2005
DOI: 10.1039/b504760a
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved gas-phase kinetic and quantum chemical studies of the reaction of silylene with oxygen

Abstract: Time-resolved kinetic studies of the reaction of silylene, SiH2, generated by laser flash photolysis of phenylsilane, have been carried out to obtain rate constants for its bimolecular reaction with O(2). The reaction was studied in the gas phase over the pressure range 1-100 Torr in SF(6) bath gas, at five temperatures in the range 297-600 K. The second order rate constants at 10 Torr were fitted to the Arrhenius equation: [see text] The decrease in rate constant values with increasing temperature, although s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 55 publications
5
63
1
Order By: Relevance
“…The results of these experiments are shown in Figures 1 and 2. Reasonable linear fits were obtained, as expected for second order kinetics, although it should be noted that there is slightly higher scatter than is usually obtained in this kind of study [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Because the rate constants showed a dependence on laser pulse energy, two plots are shown, one for higher pulse energies (60 mJ) and one for lower values (ca 30 mJ).…”
Section: Kineticsmentioning
confidence: 88%
See 1 more Smart Citation
“…The results of these experiments are shown in Figures 1 and 2. Reasonable linear fits were obtained, as expected for second order kinetics, although it should be noted that there is slightly higher scatter than is usually obtained in this kind of study [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Because the rate constants showed a dependence on laser pulse energy, two plots are shown, one for higher pulse energies (60 mJ) and one for lower values (ca 30 mJ).…”
Section: Kineticsmentioning
confidence: 88%
“…SiH 2 also has a great affinity for electronegative elements and will react with lone pair donor species containing the elements of N, O, F, P, S and Cl amongst others [4]. We, and others, have recently studied the kinetics of its reactions with "O-donor" molecules, H 2 O [5,6], CH 3 OH (CD 3 OD) [5], Me 2 O [7,8], Me 2 CO [9], MeCHO [10,11], CO [12], CO 2 [13] and O 2 [14] itself, and also with "Cldonor" molecules, HCl [15] and CH 3 Cl [16]. We have also previously reported kinetic studies of the reactions of SiH 2 with the N-containing molecules N 2 O [17], NO [18] and even N 2 [19] (although no reaction was found in this case).…”
Section: Introductionmentioning
confidence: 97%
“…From our slab (cluster) calculations the overall exothermicity of the O 2 adduction is predicted to be 3.1-3.2 (3.3) eV, consistent with previous theoretical studies that also reported high exothermicities of 2.7-4.1 eV, depending on the silylene substituents (such as :SiX 2 , X= H, CH 3 , Ph). [11,26,27] In addition, the O 2 adduct reaction tends to occur with no significant activation barrier. For instance, the reaction between SiH 2 and O 2 was observed to occur at 297-600 K. [12] For the singlet DOSG (b), the predicted OÀO/SiÀO bond distances and OÀSiÀO bond angle are 1.64 (1.63)/1.64 (1.65) and Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…[13] An O 2 molecule may readily react with the active divalent Si in SS and form a DOSG (Figure 1 b), that is, O 2 (triplet) + SS (singlet)!DOSG (singlet). Previous studies [12,[26][27][28] suggest that the O 2 adduct reaction would follow three steps. Firstly, one end of the O 2 binds to the divalent Si and forms a silanone O-oxide (> SiCOOC, where C represents a dangling bond) in which the Si becomes pyramidalized (like a silyl radical, SiC) while the Sibound O 2 (SiÀOOC) exhibits superoxo (O 2 À ) character.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation